2020
DOI: 10.20473/jaki.v8i2.2020.141-150
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Village Midwife Performance in Reducing Maternal and Infant Mortality Rate

Abstract: Background: The most essential aspect to reduce the number of maternal and newborn mortality is midwife competence. Midwives have a great role to be able to handle variety of health services (antepartum, intrapartum, and postpartum) to avoid or decrease the maternal and infant mortality rate. Performance of health workers, particularly midwives, is the most crucial in affecting the quality and quantity of midwives’ services to  enhance the national health development.Aim: This study analyzed factors affecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This could correspond to the fact that the practice of TBAs in Indonesia is the main factor for the low health facility utilization for childbirth [4]. The health system problem of inadequate referral facilities and poor infrastructure in rural areas makes many women prefer TBAs for childbirth [4], [21] This study found that specific socio-demographic factors predict women's decisions in childbirth services. Women of younger age, lower education, poor household economic condition, and unprotected health insurance coverage tend to give birth at home [22].…”
Section: Resultsmentioning
confidence: 81%
“…This could correspond to the fact that the practice of TBAs in Indonesia is the main factor for the low health facility utilization for childbirth [4]. The health system problem of inadequate referral facilities and poor infrastructure in rural areas makes many women prefer TBAs for childbirth [4], [21] This study found that specific socio-demographic factors predict women's decisions in childbirth services. Women of younger age, lower education, poor household economic condition, and unprotected health insurance coverage tend to give birth at home [22].…”
Section: Resultsmentioning
confidence: 81%
“…Aini, Purhadi and Irhamah (2020) did a similar study in Central Java Province the next year, and likewise demonstrated a substantial relationship between K1 and K4 on the risk for maternal death. The quality of antenatal care services is also inseparable from the role of health duties, especially midwives who also make an important contribution to preventing complications of death during pregnancy and childbirth (Hiola and Badjuka, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The core MCOC competencies that midwives possess are still a top priority for preventing and dealing with the causes of maternal death [ 20 ] and are hence vital in reducing maternal and newborn mortality [ 21 , 22 ]. Nonetheless, midwives still face challenges in carrying out competencies because they lack confidence, impacting their performances [ 23 ].…”
Section: Introductionmentioning
confidence: 99%